Virtual Simulation of Automatic Quality Measurement System for Tapered Roller Bearing Based on 3D Automate Software. (August 2019) - Khlil, Alhadi; Ma, B; Shi, Z
Abstract: In present years, the simulation technique has been extensively used in manufacturing processes, solving complex problems with least time, effort and cost. This paper presented a virtual simulation of automatic quality measurement system for tapered roller bearing to aid the decision-making processes, observe system operation processes and provide an initial design for constructing processes using 3D modeling process and Python programming language, the proposed system was intended to check the tapered roller bearing dimensions and to achieve the prescribed goals, the 3D model was built, the virtual environment has been created and the motion control process was applied in 3DAutomate software.